PERAN MEDIA LITERASI DAN INFORMASI DALAM PENDIDIKAN - Rahmawati, Dwi Indri; Amaliah, Eni (Jurnal El-Pustaka, 2020)
Media literacy and information are media or tools used to facilitate literacy activities and make it easier to obtain information. In the current era, we are required to be aware of media literacy and information, along with the development of technology, the easier it is for a person to get data or information from various sources. That way the more and more hoax information we get. To avoid information hoks we must be smart in using literacy and information media, therefore in educational institutions media literacy and information have a very important role. This journal writing aims to determine the role of media literacy and information in education. currently, the existence of literacy and information media is very close to education such as libraries, mass media (internet), and others. The analysis in this journal uses four steps of literature review, namely, selecting topics to be discussed, finding and selecting material related to topics from other sources of journals and books, analyzing literature, and organizing writings. The results of this literature review indicate that literacy and information media are tools or vehicles used to facilitate literacy and find information. Media literacy and information have several types, namely, library literacy media, literary and cultural literacy media, information literacy media, and many others. Media literacy and information act as an information center, innovation center, and as a center or aids to solve a problem. Besides, media literacy and information also cover all matters relating to knowledge as well as make educational institutions aware of the media.